America And the Pacific - 1994 And Beyond - Drobnick, Richard (Forum Manajemen; Vol 8 No 58 (1994): Forum Manajemen | Integrasi Perdagangan dan Redesain Bisnis Perusahaan Multinasional, 2018)
I will bein by sketching a picture of the ongoing economic integration in the Pacific Rim. (The complete introduction is on the pdf form)